STRATEGI PENINGKATAN PELAYANAN PUBLIK ANTARMODA TRANSPORTASI DENGAN KONSEP GOOD GOVERNANCE DALAM MENDUKUNG PROGRAM TOL LAUT - Karjono, Karjono; Karmanis, Karmanis; Kusumawati, Evyana Diah (Politeknik Bumi Akpelni, 2022)
The concept of improving public services formulates problems from the quality of public services in supporting the Sea Toll, Factors that become obstacles and support the improvement of service quality, relevant strategies, which aim to Know the quality of public services in supporting the Sea Toll program, know the factors that are obstacles and supporters, as well as support government programs and formulate relevant strategies in improving the quality of services public intermodal transportation. Such a change in the attitude of the community can be seen by the large number of permit applications made by the community to do business or create new business opportunities, especially in terms of transportation. People's hopes to improve their welfare by opening business opportunities to sell indutsri products from 3tp areas (underdeveloped, remote, outermost, and border) are currently very large in the era of the global economic crisis with the rampant termination of employment carried out by large companies in the era of Covid-19. The population in this study is industry players in remote, outermost, underdeveloped, (3TP) regions, which are used using a qualitative approach where data collection techniques use observation techniques, literature studies and interviews ( interviews). The data analysis used is to use a form of qualitative descriptive method. The results of the observations obtained are the ability to implement public services in carrying out and serving to provide services to help the community as promised precisely and reliably and the reliability of employees in providing services is very helpful to the community in providing the services promised, accurate and in accordance with expectations.